2015
DOI: 10.1002/14651858.cd010956.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Oral direct thrombin inhibitors or oral factor Xa inhibitors for the treatment of deep vein thrombosis

Abstract: NOACs such as DTIs and factor Xa inhibitors may be an effective and safe alternative to conventional anticoagulation treatment for acute DVT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 57 publications
0
44
0
4
Order By: Relevance
“…Finally, most patients received warfarin; although direct oral anticoagulants are now frequently used, this change should not have affected the rates of the post-thrombotic syndrome, since both types of anticoagulation are similarly effective at preventing recurrent deep-vein thrombosis. 15,37 …”
Section: Discussionmentioning
confidence: 99%
“…Finally, most patients received warfarin; although direct oral anticoagulants are now frequently used, this change should not have affected the rates of the post-thrombotic syndrome, since both types of anticoagulation are similarly effective at preventing recurrent deep-vein thrombosis. 15,37 …”
Section: Discussionmentioning
confidence: 99%
“…Limited data are available to compare these outcomes and further research is needed [5]. Non-vitamin K antagonist (VKA) oral anticoagulant (NOAC) therapy may provide benefits for patient management in ambulatory care compared with low molecular weight heparin (LMWH) overlapping with, and followed by, a VKA [6]. NOAC therapy involves oral administration, no routine coagulation monitoring requirements, a single-drug approach (with rivaroxaban and apixaban) and fewer follow-up appointments [6].…”
Section: Introductionmentioning
confidence: 99%
“…One should also take into account the level of such recommendations [2B] indicating the clinical suggestion. The above-mentioned level of recommendations arises out of the fact that the majority of phase 3 studies that were conducted met the criteria of non-inferiority studies [43][44][45]. However, as can be seen on the basis of the presented analysis and the results of the XALIA study, the recommendation of the 2016 ACCP consensus is also confirmed by the results obtained in the routine clinical practice.…”
mentioning
confidence: 74%